Implementasi Metode Market Basket Analysis Untuk Menentukan Menu Paket Penjualan Di Bius Café - Susilayani, Asrini; Putri, Eviana Tjatur; Hartono, Lies; Ardi, Mohamad (STMIK PPKIA Tarakanita Rahmawati, 2024)
A café in Tarakan City, Bius Café, is looking for sales strategies due to increasing business competition. One promotional step that a restaurant industry can take is creating package menus that are more affordable than buying items individually, making consumers happier with such menus. Bius Café, a café with a considerable number of patrons, intends to create package menus. These packages will be a combination of food and drink items from the café, taking into account how often these combinations are chosen by customers. The Apriori Algorithm is a data mining algorithm for extracting association rules. It is a type of association rule in data mining, often referred to as affinity analysis or market basket analysis. Based on the analysis results, using the Apriori algorithm to determine sales patterns shows that to form rules, the process starts with the formation of combinations from transaction analysis of 1-itemset, 2-itemset, and 3-itemset combinations that meet the support and confidence values in forming these combinations. Several transactions are selected according to the minimum support and confidence requirements, forming rules that are then ranked with the highest confidence value of 72%, which includes